"Looking back" at personal memories on Facebook: Co-constituitive agencies in contemporary remembrance practices. (22nd November 2019) - Migowski, Ana Lúcia; Fernandes Araújo, Willian
ABSTRACT: In this paper, we discuss the expression of personal memories in digital media environments. To tackle this issue, we propose a conceptualization that conceives such memories as the outcome of co-constitutive agencies that impact contemporary mnemonic practices. We look especially at sociotechnical relationships that affect the way memory contents travel temporally and through particular contexts within localized digital environments. The empirical analysis is grounded in a case study of one of the first memory-oriented features released by Facebook in 2014, the Look Back video. We asked Facebook users to answer a questionnaire about the experience of using this feature, providing insights into the production and consumption of digital mnemonic products. Our findings point to the fact that digital traces left by users in their networks interact with the performative properties of communication systems. These interactions are articulated in mnemonic products that inspire reflections on the agency of algorithms and the meaningfulness of the resulting narratives. Acknowledging the consequences of the "third memory boom" accompanying the emergence of the connective turn in memory studies, we suggest that current digital technologies demand a more comprehensive analysis of the constellation of actors and values involved in current memory processes.